PENGARUH VOLUME PERDAGANGAN SAHAM DAN HARGA SAHAM TERHADAP BID-ASK SPREAD STUDI PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nainggolan, Ruminsar; Silalahi, Donalson (Jurnal Manajemen dan Bisnis, 2016)
ABSTRACT The purpose of this study is to determine the effect of stock trading volume and stock prices on bid-ask spreads on manufacturing companies listed on the Indonesia Stock Exchange. The population in research is 155 companies and by using purposive sampling as sampling technique, then the sample in this research is 46 company. The data used are secondary data and use multiple regression equation as an analytical tool. Based on the results of the research it can be argued that, trading volume and stock prices have a negative and significant effect on the bid-ask spread both before and after the data grouping. The results also show that stock trading in Indonesia Stock Exchange is liquid. Investors or potential investors who want to invest in the capital market should make trading volume and stock price as a reference in making investment decisions, because simultaneously these two variables have a significant effect on bid-ask spreads.